Implementasi Prinsip Syariah dalam Praktik Pembiayaan Murabahah di Koperasi Jasa Keuangan Syariah BMT Agam Madani Pakan Sinayan Kabupaten Agam - Nala Anggraini; Rahmi (ARZUSIN, 2026)
Although the implementation of Sharia principles in murabahah bil wakalah financing at Islamic microfinance institutions has been widely studied, research specifically analyzing the conformity of such contract implementation at KJKS BMT Agam Madani Pakan Sinayan remains limited. This study aimed to analyze the implementation of Sharia principles in murabahah bil wakalah financing practices at KJKS BMT Agam Madani Pakan Sinayan, Agam Regency, and identify their conformity with Sharia provisions. The study employed a qualitative approach with a case study design. The research informants consisted of the management of KJKS BMT Agam Madani and financing recipient members selected through purposive sampling. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that, in general, murabahah bil wakalah financing had been implemented in accordance with the applicable operational procedures, including financing applications, feasibility analysis, the granting of authority (wakalah), the purchase of goods, the execution of the murabahah contract, and installment payments. However, in several cases, the wakalah and murabahah contracts were executed simultaneously before the goods had, in principle, become the property of the institution; therefore, the practice was not yet fully compliant with Sharia provisions. These findings emphasize the importance of consistently implementing Sharia compliance at every stage of financing, particularly by ensuring the proper sequence of contract execution and the ownership status of the goods. This study contributes to the development of Islamic economics studies and provides practical implications for Islamic microfinance institutions in evaluating and improving the quality of financing implementation to ensure compliance with Sharia principles.